The Phenomenon and Ethics of Artificial Intelligence in Shaping Youth Worldview - Gulyamov Shavkat Makhmudovich (Web of Scientist International Scientific Research Journal, 2025)
The phenomenon of artificial intelligence (AI) has become a central focus in discussions about the digital transformation of society, particularly in how it shapes the worldview of younger generations. This paper explores the ethical implications of AI development and its influence on youth perception, decision-making, and value formation. While some experts argue that digital ethics is simply traditional ethics in a new context, others emphasize the unique challenges posed by autonomous AI systems. The discussion includes philosophical perspectives, such as those of Ludwig Feuerbach and Norbert Wiener, and touches on contemporary debates, including concerns about AI autonomy and its potential to either support or threaten human well-being. The paper argues for a comprehensive metaethical framework and regulatory principles to ensure responsible AI integration into human life